The effects of internal and external barriers on Vietnamese students’ entrepreneurial intention - Le Trung Thanh (Management Science Letters, 2020)
This study aims to investigate the effects of internal barriers, including personal traits and cognitive condi-tions, and external barriers, including normative and regulative structures, on entrepreneurial intention among Vietnamese students. By collecting data from 437 students at high schools, universities and colleges in Vietnam, authors employ a quantitative method such as certain descriptive statistics, explorative analysis (EFA), KMO and Bartlett test, correlation coefficient analysis, and logistic regression to examine the relationship be-tween entrepreneurial barriers with different issues including personal traits, cognitive condition, normative and regulative structures, and entrepreneurial intention. The research results show that all four independent variables; namely barriers related to personal traits, cognitive condition, normative and regulative structures had negative effects on entrepreneurial intention. Particularly, cognitive conditions are seen as the most influential barrier to entrepreneurial intention, followed by personal traits, regulative and normative structures.